A smartphone-supported portable micro-spectroscopy/imaging system to characterize morphology and spectra of samples at the microscale. Issue 33 (12th August 2020) - Chen, Gang; Chai, Hui Hui; Fu, Jing Jing; Yu, Ling; Fang, Can
Abstract : A novel portable smartphone-based micro-spectroscopy/imaging system comprising a mini wireless spectrometer as an optical sensor and a compact homemade microscope to precisely acquire the spectra and image of micron-scale regions. Abstract : A smartphone-based analysis system is favored for point-of-care testing applications. The present work proposes a novel micro-spectroscopy/imaging system comprising a portable spectrometer as an optical sensor and a compact homemade microscope to acquire the image and spectra of micron-scale regions. Protein concentration quantification based on the bicinchoninic acid method was demonstrated with the proposed micro-spectroscopy/imaging system to analyse the spectrometer signals. Morphologies of onion endothelial and human breast cancer cells, used as biological sample models, were characterized to demonstrate the microscopic imaging capacity of the device. The ability to simultaneously obtain morphological and spectral information using the proposed portable device was demonstrated by examining the 10 μm sub-pixels of a smartphone screen. These results highlight the potential for adopting a smartphone-based micro-spectroscopy/imaging system for point-of-care testing.